Factors that Affect Aquaculture Business Income and Koi Cultivation Development Strategy in Kemloko Village, Nglegok District, Blitar Regency - Azilla, Erina Nur; Supriono, Agus; Ridjal, Julian Adam; Rahman, Rena Yunita; Kuntadi, Ebban Bagus (Agrikan Jurnal Agribisnis Perikanan, 2024)
The decline in production has an impact on koi farming in Kemloko Village because the largest number of koi fishery business households in Blitar is Kemloko Village. So that the decline in production will indirectly affect the income of koi farmers in Kemloko Village. The objectives of the study included to determine the income and efficiency, to determine the factors that affect the income of koi cultivation, and to determine the development strategy of koi cultivation. This research uses income analysis and efficiency analysis, multiple linear regression analysis, and SWOT analysis. The results showed that the income of koi fish farmers in Kemloko Village was profitable with an average income of Rp.7,870,947/700 m3. The results showed that the income of koi fish farmers in Kemloko Village was profitable with an average income of Rp.7.870.947/700 m3/cycle and the R / C ratio value of 2.38>1, the factors that had a significant effect on the income of koi fish farming in Kemloko Village included feed costs, drug and vitamin costs, water treatment costs, selling prices, total production, and land area, while the variables that were not significant were labor costs and seed costs, the development strategy for koi ornamental fish farming in Kemloko Village using SWOT analysis obtained an IFAS value of 2.98 and an EFAS value of 2.94 and using an alternative strategy using the SO strategy.